2016
DOI: 10.1590/s2179-975x0316
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure of macroinvertebrates in tropical pasture streams

Abstract: Aim The aim of this study was to describe the diet of stream macroinvertebrates and to determine their trophic groups. Methods Invertebrates were sampled with D nets in three pasture streams. They were identified to genus level and submitted to gut content analysis, except for fluid feeders such as hemipterans, to which diet data was obtained from the literature. Trophic groups were determined based on a similarity analysis using the Bray-Curtis similarity coefficient. Results Five trophic groups were define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This is mainly due to the fact that the most abundant families (Hydropsychidae, Philopotamidae and Simuliidae) are mostly collector-filters. However, it is important to highlight that some families or groups may have a generalist habit, adapting to food resources availability (Silveira-Manzotti et al 2016). De Castro et al (2016) found that changes in land use, such as the cultivation of sugar cane and livestock, can lead aquatic macroinvertebrate assemblages to exhibit more generalist feeding habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the fact that the most abundant families (Hydropsychidae, Philopotamidae and Simuliidae) are mostly collector-filters. However, it is important to highlight that some families or groups may have a generalist habit, adapting to food resources availability (Silveira-Manzotti et al 2016). De Castro et al (2016) found that changes in land use, such as the cultivation of sugar cane and livestock, can lead aquatic macroinvertebrate assemblages to exhibit more generalist feeding habits.…”
Section: Discussionmentioning
confidence: 99%
“…Studying them is important because the macrobenthic organisms are known as indicators of anthropogenic stress due to their sedentary habitat. Furthermore, they maintain various levels of interaction between the community and environment (Bieger et al 2010;Silveira-Manzotti et al 2016;Brraich and Kaur 2017). The structure of the aquatic macroinvertebrate community provides precise and local information on recent events.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that the specific characteristics of the plateau area, such as higher current rivers and, in some areas, natural grasslands, do not favor this trophic group. However, caution is required in the interpretation of this index for a plateau region, as it has never been applied to this area and other studies in southern Brazil were conducted under different phytophysiognomic and climatic conditions (CUMMINS et al, 2005;SILVEIRA-MANZOTTI et al, 2016;FERREIRA et al, 2017;PEREIRA et al, 2017a;FAVRETTO et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the presence of FPOM (detritus) in the stomach contents of the Phylloicus larvae may be related primarily to the availability of this material in the habitat (Henriques-Oliveira et al, 2003;Chará-Serna et al, 2012). This reinforces the importance of this food resource in tropical freshwater ecosystems (Palmer et al, 1993;Motta & Uieda., 2004;Ceneviva-Bastos & Casatti, 2014;Silveira-Manzotti et al, 2016), related to microbial activity, which accelerates decomposition, increasing the nutritional quality of this detritus for these invertebrates (Robinson et al, 1998;Graça, 2001).…”
Section: Discussionmentioning
confidence: 99%